Stability of hydrophobic colloids: Perspectives and current opinion. Issue 4 (1st March 2021) - Rakshit, Animesh Kumar; Naskar, Bappaditya; Moulik, Satya Priya
Abstract: Stability of hydrophobic colloids is an important phenomenon in colloid science. The hydrophobic colloids are known to get destabilized by the counterions of electrolytes leading to coagulation guided by Schulze–Hardy (S-H) rule. There are exceptions to this rule; effective improvement has been attempted but not with good success. Recently, the role of coions in the coagulation process was considered: an inverse Schulze–Hardy (iS-H) rule has been proposed. We have discussed the basics of colloid solutions, and colloid stability: also have tested the S-H and iS-H rules in terms of a number of positively and negatively charged hydrophobic colloids. Critical coagulation concentrations, zeta-potential, charges of coions and counterions, and ionic strengths have been separately (as well as together) considered to correlate the coagulation phenomenon. Partial agreements with the rules are only found. The article summarizes the fundamentals of the field of colloid stability, and its current status. Analysis of experimental findings in a new perspective (in terms of a new analytical procedure) has been proposed with a view to its projection toward future studies. Graphical Abstract: